1981
DOI: 10.1063/1.442532
|View full text |Cite
|
Sign up to set email alerts
|

57Fe-Mössbauer studies of the CuxFe3−xO4 spinel system

Abstract: Mössbauer spectroscopy has been used to examine the effect of increasing copper ion concentration on the iron distribution in CuxFe3−xO4(0⩽x⩽0.9). For x⩽0.37, fast electron exchange among octahedral iron ions occurs as in Fe3O4, suggesting that the itinerant electrons associated with the octahedral Fe2+ ions remain delocalized in the sublattice. At high values of x (x⩾0.59), however, the itinerant electrons become localized in a small fraction of exchange-coupled iron ions. The relative numbers of distinguisha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A third sextet is observed, centered at a lower field of H3=46.2 T and asymmetrically broadened, indicating a distribution of hyperfine fields. This may be due to the formation of the solid solution Cu x Fe 3-x O 4 with an extended range of x, where the different Fe 3+ environments result in the observed hyperfine field distribution (22).…”
Section: Resultsmentioning
confidence: 99%
“…A third sextet is observed, centered at a lower field of H3=46.2 T and asymmetrically broadened, indicating a distribution of hyperfine fields. This may be due to the formation of the solid solution Cu x Fe 3-x O 4 with an extended range of x, where the different Fe 3+ environments result in the observed hyperfine field distribution (22).…”
Section: Resultsmentioning
confidence: 99%
“…The small hyperfine field and broad lines are related to sample regions with oxygen vacancies and/or high local disorder produced during milling. We associate these features with the formation of sample regions with Cu x Fe 3−x O y stoichiometry (see discussion below) [21].…”
Section: Resultsmentioning
confidence: 99%
“…Other authors also have suggested the simultaneous appearance of octahedral Fe 2 .5+ and Fe3+ subpatterns, the latter one arising from ferric ions that do not participate in the charge transfer and therefore being unresolved from the A-site component. [385][386][387][388] Commonly, these conclusions were arrived at on the basis of the observation that the area ratio SAl SB is considerably different from the value expected from the known cation distribution. Clear-cut evidence that unpaired Fe 3 + ions on octahedral sites of substituted magnetites indeed do exist was provided by high-field M6ssbauer measurements on nonstoichiometric Fe304/76,389 on COXFe3_X04,390 and on Lio.5(1_X)Fe2.5+0.5X04,391 in which cases an additional four-line pattern, with parameters typical for Fe~+, has to be included in the fit.…”
Section: Magnetite and Substituted Magnetitesmentioning
confidence: 99%
“…AI20 3,381,383,386,387,389f FeAl20 4,87 FeB,276 Fe3B,21Of Fe7J324,208 FesoB20,190,273 FexB100' 276f Subject Index FeB03,255,257,267f FeSlB\3.5Si3.5CZ,192f,207f Fe3C,211,34lf Fe5CZ,34lf FesoCzo,273 FeCoCr04,99 Fe70C07oM030Si3oB30,272 Fe5C055Nizo(SiBho,272 FeCoZ0 4,78 FeZ.97C00.Q304,74 (Feo.zCOO.8)801'17AI3,204 FeCoSiB,276 (Fel_zCozhSiB,282 (Fel_zCozhSiB,282 FexC07S_xSi9B13,276,279 Fe4C074Si9B13,282 Fe5SCozoSi9Bl3,279 FeCrZ04,86,92,105,113 FeZCr04,93 Fe I.5Cr 1.5°4,289 FeGez,471 FesoGezo,273 Fez.4z5Lio.5z5Sllo.0504,…”
Section: Section 12 Binary Intermetallic Compoundsmentioning
confidence: 99%